The role of TRPM8 in the pathophysiology of migraine - Nogueira, Eduardo de Almeida Guimarães; Fragoso, Yara Dadalti (Headache Medicine, 2020)
The Transient Receptor Potential Melastatin 8 (TRPM8) is a member of the mammal TRPM subfamily. TRPM8 is involved in menthol-induced cold allodynia, a condition that activates the left lateral thalamus and the primary and secondary somatosensory cortices, which are related to pain processing. Cold is a well-known trigger of migraine. Thirty-nine articles were identiﬁed, 27 of which were selected for review after reading the abstracts. Fourteen papers were further excluded. TRPM8 seems to be involved in the pain mechanism of migraine and therefore should be considered as a target for the development of therapies against this type of primary headache.